Microbiota-targeted therapies in inflammation resolution. (January 2022) - Strati, Francesco; Lattanzi, Georgia; Amoroso, Chiara; Facciotti, Federica
Graphical abstract: Highlights: The gut microbiota regulates the susceptibility to intestinal and extra intestinal diseases modulating host immunity and inflammation. Manipulation of the microbiota improve inflammation and disease outcome. The translational value of the microbiota is demonstrated by the efficacy of new microbiota-targeted therapies. Abstract: Gut microbiota has been shown to systemically shape the immunological landscape, modulate homeostasis and play a role in both health and disease. Dysbiosis of gut microbiota promotes inflammation and contributes to the pathogenesis of several major disorders in gastrointestinal tract, metabolic, neurological and respiratory diseases. Much effort is now focused on understanding host-microbes interactions and new microbiota-targeted therapies are deeply investigated as a means to restore health or prevent disease. This review details the immunoregulatory role of the gut microbiota in health and disease and discusses the most recent strategies in manipulating individual patient's microbiota for the management and prevention of inflammatory conditions.